Papering over the cracks: COVID-19's amplification of the failures of employer-based health insurance coverage. Issue 1 (2nd January 2021) - Ramgobin, Devyani; McClafferty, Brendan; Kramer, Courtney; Golamari, Reshma; McGillen, Brian; Jain, Rohit
ABSTRACT: Background : COVID-19 has altered numerous lives and accounted for significant mortality and morbidity throughout the world and, especially, the USA. During the pandemic, from mid-March to July 2020, around one-fourth of the US population filed for unemployment benefits. Objective : In this article, we discuss the economic ramifications exposed in the American healthcare system's current model by the COVID-19 crisis. Methods : In this review, we analyze 18 articles to look at how access to health insurance has affected how Americans receive medical care during the coronavirus pandemic. Results : The large-scale job losses related to the pandemic translates directly into millions of Americans also losing employer-sponsored health insurance (ESI) coverage. With the pandemic disproportionately affecting minority populations, these communities now bear the additional toll of not receiving appropriate care. Conclusion : Due to the pandemic, it is probable that a significant portion of Americans that are uninsured are less likely to seek medical care for COVID-19 symptoms. While the disease can manifest as a mild respiratory illness in most, others can experience more severe disease and require acute, intensive medical care. The lack of health insurance in this instance can be potentially fatal. Given that COVID-19 has disproportionately affected minority communities across the USA, it is important to highlight the correlation between access to medical care and COVID-19 infection rates. Communities that are of lower socioeconomic status are less likely to have health insurance and follow up with medical care due to out-of-pocket costs, which in turn leads to a higher case fatality rate due to COVID-19.